2005
DOI: 10.1111/j.1467-6494.2005.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Correlates of Heroic Rescue During the Holocaust

Abstract: This study investigated the extent to which personality variables can be used to discriminate non-Jewish heroes of the Holocaust from bystanders and from a comparison group of prewar European immigrants who left their countries of origin prior to World War II. Eighty verified rescuers, 73 bystanders, and 43 immigrants were administered measures of locus of control, autonomy, risk taking, social responsibility, tolerance/authoritarianism, empathy, and altruistic moral reasoning. A three-group discriminant funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Individuals with an external locus of control tend to conform to the status quo and are less likely to report instances of ethical misconduct in organizations (Dozier & Miceli, 1985;Near & Miceli, 1996). They are also less likely to participate or help in high-risk settings (e.g., Bierhoff et al, 1991;Guagnano, 1995;Midlarsky, Fagin-Jones, & Corley, 2005;Midlarsky & Kahana, 1994;Oliner & Oliner, 1988). Luthans et al (1998) noted that many citizens of the former Soviet Union have internalized a sense of helplessness, as evidenced in their continued vulnerability to destructive leaders and failure to take control and escape their oppressive past.…”
Section: Negative Core Self-evaluationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals with an external locus of control tend to conform to the status quo and are less likely to report instances of ethical misconduct in organizations (Dozier & Miceli, 1985;Near & Miceli, 1996). They are also less likely to participate or help in high-risk settings (e.g., Bierhoff et al, 1991;Guagnano, 1995;Midlarsky, Fagin-Jones, & Corley, 2005;Midlarsky & Kahana, 1994;Oliner & Oliner, 1988). Luthans et al (1998) noted that many citizens of the former Soviet Union have internalized a sense of helplessness, as evidenced in their continued vulnerability to destructive leaders and failure to take control and escape their oppressive past.…”
Section: Negative Core Self-evaluationsmentioning
confidence: 95%
“…Prior research on mass genocide, namely the Holocaust, indicates that, unlike bystanders, rescuers maintained a courageous-prosocial disposition characterized by increased levels of empathic concern, altruistic moral reasoning, social responsibility, and risk-taking (Fagin-Jones & Midlarsky, 2007;London, 1970;Midlarsky & Kahana, 1994;Midlarsky et al, 2005;Oliner & Oliner, 1988;Staub, 2005). Together, these characteristics form the backbone of valor, kindness, and self-sacrifice (Peterson & Seligman, 2004), and are believed to be necessary for helping in high stress situations involving the potential for high personal costs to the actor.…”
Section: Lack Of a Courageous-prosocial Dispositionmentioning
confidence: 96%
“…Although some scholars have gone so far as to argue that moral behavior is totally determined by the situation (Doris, 1998;Harman, 2003), a substantial body of empirical research shows that stable individual characteristics also matter. Midlarsky, Fagin Jones, and Corley (2005) found that holocaust rescuers were distinguishable from a comparison group of bystanders on the basis of personality variables, including internalized altruistic values, a sense of social responsibility, and empathic concern. In another study, Walker and Frimer (2007) found that personalityrelated themes like agency and communion were more prevalent in the life narratives of moral exemplars-people who have been recognized for their moral actions-as compared against a demographically matched comparison group.…”
mentioning
confidence: 99%
“…That is to say, why do individuals voluntarily act to promote the well-being of others without request for, or expectation of, reward. A substantial body of social psychological research has demonstrated that altruism is motivated by humanistic ideology, personality, affect, and social modeling (e.g., Batson and Shaw 1991;Johnson et al 1989;Lee et al 2005;Mattis et al, under review;Midlarsky et al 2005;Oliner and Oliner 1988;Smolenska and Reykowski 1992;Underwood and Moore 1982). A smaller body of scholarship has highlighted the role of race, ethnicity, gender, and urbanicity in the development of altruistic forms of helping (e.g., Baron 1992;Becker, and Eagly 2004;Bridges, and Coady 1996;Butovskaya et al 2004;Zaleski 1992).…”
Section: Introductionmentioning
confidence: 97%